P.018 Minimally invasive endoscopic evacuation of intraparenchymal hematomas, a single centre experience. (2nd June 2017) - Deis, NP; Ryan, R; Pham, A
Abstract : Background: Patients with spontaneous intracerebral hemorrhage (ICH) suffer significant morbidity and mortality with lengthy critical care and hospital stays. Minimally invasive techniques for ICH removal have shown a positive relationship between hemorrhage volume reduction and patient outcome. We describe our single centre experience with endoscopic assisted, neuronavigation guided ICH evacuation using the Apollo system.Methods: Patients with ICH treated with the Apollo system since October 2014 were included in this retrospective review. ICH volume, clot reduction, midline shift, ICU and hospital length of stay, discharge disposition and last known functional outcome were assessed.Results: 58 patients were treated, mean age 54.1 years. Starting clot volume was 55.1±30.5cc, which was reduced to 10.2±12cc post-operatively, an average reduction of 80.6±25%. Midline shift improved from 7.1±4.5mm to 4.4±3.2mm. Length of ICU stay was 10.2±7.6 days. Covariate analysis showed greater relative reduction in ICH volume correlated with shorter ICU stay (p=0.01). In-hospital mortality was 27.3%; 29.1% of patients were discharged home either form hospital directly, or after a period of short-stay rehab.Conclusions: Significant hematoma volume reduction and improvement in midline shift is possible with the Apollo system. Degree of reduction of hematoma volume was associated with a shorter ICU Stay. Randomized controlled studies will be required to determine long term clinical benefit.